The influence of Propylene glycol/Water and Ethanol/Water Binary Solvents on the in vitro Permeation of Garcinia mangostana L. Pericarp Extract across Shed Snakeskin - Kuswahyuning, Rina; Sulaiman, TN Saifullah; Wahyu Ananingrum, Galuh; Reno Andini, Rias (Indonesian Journal of Pharmacy, 2020)
Garcinia mangostana pericarp (GMP) has antioxidant activity thus may be developed into a topical antioxidant formulation. This research aimed to study the topical delivery of GMP extract. Initially, some commonly used topical solvents, i.e., water and binary solvents of propylene glycol (PG)/water and ethanol/water (0; 10; 20 and 40%), were used to dissolve GMP extract and further tested on GMP extract in vitro skin permeation using shed snakeskin. The influence of solvents’ effects was evaluated based on radical DPPH scavenging activity and expressed as radical scavenging activity equivalent GMP Extract (RSGMPE). The results showed that RSGMPE could be delivered into shed snakeskin. The extent of RSGMPE shed snakeskin retention was similar among water and all PG/water or ethanol/water binary solvents. RSGMPE was also found in the receptor phase from all PG/water binary solvents, whereas that from ethanol/water solvents only shown from 20% ethanol/water solvent even though all ethanol-water solvents produced significantly higher RSGMPE compared to water and PG/water binary solvents